Pseudouridylation of helix 69 of 23S rRNA is necessary for an effective translation termination - Ejby, Morten (National Academy of Sciences, 2007)
Escherichia coli strains with inactivated rluD genes were previously found to lack the conserved pseudouridines in helix 69 of 23S ribosomal RNA and to grow slowly. A suppressor mutant was isolated with a near normal growth rate that had changed the conserved Glu-172 codon to a Lys codon in prfB, encoding translation termination factor RF2. When nonsense suppression in strains with all combinations of prfB(+)/prfB(E172K) and rluD(+)/rluD::cat was analyzed, misreading of all three stop codons as sense codons was found to be increased by rluD inactivation: Nonsense suppression was increased 2-fold at UAG codons, 9-fold at UAA, and 14-fold at UGA. The increased read-through at UGA corresponds to reading UGA as a sense codon in 30% of the cases. In contrast, the accuracy of reading sense codons appeared unaffected by loss of rluD. When the inactivated rluD gene was combined with the altered prfB, wild-type levels of termination were restored at UAA codons and termination was more efficient than wild type at UGA. These results strongly suggest that at least one of the helix 69 pseudouridines has a function in translation termination. To our knowledge, this is the first described function for a ribosomal RNA pseudouridine modification.